Gender aspect in primary mathematics - Kiseliova, Danutė; Kiseliovas, Arkadijus (Lietuvos matematikos rinkinys, 2003)
The research results show that the girls of the fourth form solve mathematics tasks better than boys from the qualitative point of view. However, a statistically significant difference was received in solving only the tasks on measurements (x2 = 8.6, p < 0.05) and applications (x2 = 7.94, p < 0.05).